2021
DOI: 10.1017/s0007114521003251
|View full text |Cite
|
Sign up to set email alerts
|

The role of a Mediterranean diet and physical activity in decreasing age-related inflammation through modulation of the gut microbiota composition

Abstract: Chronic inflammation is known to be a predominant factor in the development of many age-related conditions including cardiovascular disease, type II diabetes and neurodegenerative diseases. Previous studies have demonstrated that during the ageing process there is an increase in inflammatory biomarkers, which may be partially brought about by detrimental changes to the gut microbiota. The Mediterranean diet (MedDiet) and physical activity are protective against inflammation and chronic disease, and emerging ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 141 publications
0
13
0
Order By: Relevance
“…140 Notably, the Mediterranean diet, one of the healthiest dietary patterns, is characterized by abundant vegetable food and significantly decreases the risk of developing late-onset CD by positively regulating the composition and metabolism of gut microbiota. 143 Several studies have demonstrated the significantly positive variation of gut microbiota after intervention of the Mediterranean diet, observed by increased abundances of beneficial bacteria and decreased abundances of harmful bacteria. 143 Compared to that with other formulated diets, IBD patients on Mediterranean diet may be less susceptible to malnutrition, 144 suggesting that the Mediterranean diet is a potential intervention for IBD prevention.…”
Section: Dietary Intervention Reduces Risk Of Ibd By Regulating Gut M...mentioning
confidence: 99%
“…140 Notably, the Mediterranean diet, one of the healthiest dietary patterns, is characterized by abundant vegetable food and significantly decreases the risk of developing late-onset CD by positively regulating the composition and metabolism of gut microbiota. 143 Several studies have demonstrated the significantly positive variation of gut microbiota after intervention of the Mediterranean diet, observed by increased abundances of beneficial bacteria and decreased abundances of harmful bacteria. 143 Compared to that with other formulated diets, IBD patients on Mediterranean diet may be less susceptible to malnutrition, 144 suggesting that the Mediterranean diet is a potential intervention for IBD prevention.…”
Section: Dietary Intervention Reduces Risk Of Ibd By Regulating Gut M...mentioning
confidence: 99%
“…Dietary factors are related to chronic disease risk, and they have been suggested to modulate the composition and function of the gut microbiome [56,57 ▪▪ ]. Healthy dietary habits, such as the Mediterranean diet, cantered on fruits, vegetables, legumes, nuts, olive oil, and whole grains, are associated with the promotion of good health, and emerging evidence has shown that these effects may be partially mediated through beneficial changes in the gut microbiota [58].…”
Section: Microbiota-targeted Interventions For Healthy Ageingmentioning
confidence: 99%
“…Adherence to a MDP, for 6 months, improved dietary inflammatory status and fatigue severity in RRMS patients relative to the TID (19) . As reviewed by Clark and colleagues the protective effects of the MDP https://doi.org/10.1017/S0007114522002471 Published online by Cambridge University Press Accepted manuscript against inflammation may be in part mediated through favourable changes to the gut microbiota composition and activity (20) .…”
Section: A Mdp Inflammation and Other Chronic Conditionsmentioning
confidence: 99%
“…Adherence to a MDP for 6 months improved dietary inflammatory status and fatigue severity relative to the traditional Iranian diet (19) . As reviewed by Clark and colleagues, the protective effects of the MDP against inflammation may be in part mediated through favourable changes to the gut microbiota composition and activity (20) .…”
Section: A Mdp Inflammation and Other Chronic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation